HUBUNGAN KASIH SAYANG DIRI SENDIRI TERHADAP STATUS KESEHATAN MENTAL PADA LANSIA DI KELURAHAN AIR TIRIS KECAMATAN KAMPAR - ALINI ALINI (Universitas Pahlawan Tuanku Tambusai, 2020)
Mental health status is a mental state or psychological state that is disturbed marked by problems that exist within oneself (internal) and problems that exist in the external environment (external). One cause of disturbed mental health status is self-affection. The purpose of this study was to determine whether there is a relationship of self-affection to the mental health status of the elderly in Air Tiris Village, Kampar District. This research is a quantitative study with cross sectional design. The sample in this study were some of the elderly who were in Air Tiris Village, Kampar District, totaling 79 people with simple random sampling technique. Data processing uses the chi-square test. The results showed that there was no significant relationship between self-affection towards mental health status in the elderly in Air Tiris Village, Kampar Subdistrict (p value> Î± (0.05). The results of this study were expected to be used by the elderly to further improve worship. and get closer to Allah SWT and follow the activities carried out by elderly groups such as mothers' recitation.